2020
DOI: 10.1016/j.ejphar.2020.173644
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for COVID-19: An overview

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by coronavirus-2 (SARS-CoV-2) that causes a severe acute respiratory syndrome, a characteristic hyperinflammatory response, vascular damage, microangiopathy, angiogenesis and widespread thrombosis. Four stages of COVID-19 have been identified: the first stage is characterised by upper respiratory tract infection; the second by the onset of dyspnoea and pneumonia; the third by a worsening clinical scenario dominated by a cytokine storm and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
263
0
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(286 citation statements)
references
References 20 publications
4
263
0
19
Order By: Relevance
“…Despite the recent development of vaccines to prevent the disease, new therapeutic alternatives to treat the established disease should be studied [ 38 , 39 ]. According to the pathological characteristics of COVID-19 and different clinical stages, especially for patients with moderate to severe disease, antiviral agents, inflammation inhibitors/antirheumatic drugs, low molecular weight heparins and convalescent plasma with high IgG titers against SARS-CoV-2 have been used and tested [ 9 , 10 , 11 ]. In the early stages of the disease, the treatment of COVID-19 remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the recent development of vaccines to prevent the disease, new therapeutic alternatives to treat the established disease should be studied [ 38 , 39 ]. According to the pathological characteristics of COVID-19 and different clinical stages, especially for patients with moderate to severe disease, antiviral agents, inflammation inhibitors/antirheumatic drugs, low molecular weight heparins and convalescent plasma with high IgG titers against SARS-CoV-2 have been used and tested [ 9 , 10 , 11 ]. In the early stages of the disease, the treatment of COVID-19 remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pathological characteristics of COVID-19, especially for patients with moderate to severe COVID-19, several treatment strategies have been developed, including, among others, antiviral agents, inflammation inhibitors/antirheumatic drugs and low molecular weight heparins [ 9 , 10 ]. Concerning new therapies, it is necessary to highlight the administration of convalescent plasma with high IgG titers against SARS-CoV-2, which have revealed promising results, although further studies are required [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 produced by activated macrophages is known to be a critical mediator of lung injury in COVID19 patients [54]. This cytokine is responsible for recruitment and activation of inflammatory cells and is closely associated with the hyperimmune response observed in patients characterized by severe infiltration of macrophages and lymphocytes into lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs utilized for COVID-19 involve broad-spectrum antiviral agents, for instance HIV-protease inhibitors and nucleoside analogues. According to recent articles, broad-spectrum antiviral drugs, containing neuraminidase inhibitors, lopinavir, RNA synthesis inhibitors and peptides, are regarded rational for the treatment method [ 3 ]. Ledford et al [ 4 ] has observed that dexamethasone is the first drug to be proven to decrease the deaths caused by COVID-19.…”
mentioning
confidence: 99%